1994
DOI: 10.1523/jneurosci.14-10-06256.1994
|View full text |Cite
|
Sign up to set email alerts
|

Increased glutamate decarboxylase mRNA levels in the striatum and pallidum of MPTP-treated primates

Abstract: The mRNA levels encoding for the enzyme glutamate decarboxylase (GAD67) were measured by computerized image analysis after in situ hybridization histochemistry and radioautography in the striatum and pallidum of normal squirrel monkeys (Saimiri sciureus), or after treatment with the neurotoxin 1-methyl-4-phenyl-1,2,3,6- tetrahydropyridine (MPTP). All MPTP-injected monkeys exhibited profound motor deficits including akinesia. The dopaminergic innervation, as visualized and quantified on x-ray films after 3H-maz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 33 publications
7
30
0
Order By: Relevance
“…As previously reported Soghomonian et al, 1994), the intensity of labeling with the radioactive GAD67 or GAD65 probes was higher in MPTP-treated than in control monkeys (Figs. 3, 4).…”
Section: Distribution Of Gad67/gad65 Mrna Labeling In Ppe-labeled Andsupporting
confidence: 86%
See 1 more Smart Citation
“…As previously reported Soghomonian et al, 1994), the intensity of labeling with the radioactive GAD67 or GAD65 probes was higher in MPTP-treated than in control monkeys (Figs. 3, 4).…”
Section: Distribution Of Gad67/gad65 Mrna Labeling In Ppe-labeled Andsupporting
confidence: 86%
“…Such lesions also alter the striatal gene expression of the g-aminobutyric acid (GABA)-synthesizing enzyme, glutamate decarboxylase (GAD), which exists as two isoforms of different molecular weight, GAD65 and GAD67. Thus, increases in GAD67 and/or GAD65 gene expression in the putamen and, to a lesser extent, in the caudate nucleus have been recently reported in MPTP-treated monkeys Soghomonian et al, 1994Soghomonian et al, , 1996. Increased striatal GAD67 gene expression has also been observed in rats with 6-hydroxydopamine (6-OHDA) lesions of dopamine neurons (Segovia et al, 1990;Soghomonian et al, 1992;Vernier et al, 1988).…”
Section: Introductionmentioning
confidence: 95%
“…It is therefore most likely that the increased level of GAD protein in GPi represents increased activity of local axon collaterals of GPi neurons and is therefore another indicator that GPi activity is enhanced in MPTP-treated animals. This is also suggested by studies that have demonstrated that GAD mRNA levels in GPi are increased in parkinsonism Soghomonian et al, 1994;Herrero et al, 1996a;Salin et al, 2002;Schneider and Wade, 2003).…”
Section: Global Neuronal Activity Changes In Parkinsonismmentioning
confidence: 68%
“…This hypothesis, which implies hypoactivity of the GP in PD state (Albin et al, 1989;DeLong, 1990), does not fit however with recent reconsideration of GP function in the BG circuitry (Levy et al, 1997). The expression of the GABA-synthesizing enzyme GAD67 is enhanced in the GP rather than decreased after extensive unilateral DA denervation (Kincaid et al, 1992;Soghomonian and Chesselet, 1992;Soghomonian et al, 1994;Nielsen and Soghomonian, 2003). In contrast, pallidal expression of cytochrome oxidase subunit I (COI), a metabolic index of neuronal activity, was not enhanced after partial DA denervation (Oueslati et al, 2005).…”
Section: Group III Mglurs Activation In the Globus Pallidus Produces mentioning
confidence: 98%